2021
DOI: 10.1016/j.rmcr.2021.101383
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serial lung ultrasound for a severe COVID-19 patient on extracorporeal membrane oxygenation

Abstract: Computed tomography (CT) is the most reliable method to evaluate the progression of COVID-19 pneumonitis. However, in a pandemic, transportation of critically ill invasively ventilated patients to radiology facilities is challenging, especially for those on extracorporeal membrane oxygenation (ECMO). Notably, lung ultrasound (LUS) is a favored alternative imaging modality due to its ease of use at the point of care, which reduces the infectious risk of exposure and transmission; repeatability; absence of radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Recently, it has been shown that LUS ndings are similar to chest CT ndings, and they are superior to chest radiography ndings for evaluating patients with COVID-19 [36,37]. Indeed, we reported the usefulness of LUS as the sole imaging modality with bedside accessibility to patients for the timely identi cation of pulmonary condition, thus reducing the risk of moving unstable ECMO patients [14]. Furthermore, de Almeida Monteiro et al showed a histological background that supports the fact that LUS can be used to characterise the progression and severity of lung damage in severe COVID-19 [38].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recently, it has been shown that LUS ndings are similar to chest CT ndings, and they are superior to chest radiography ndings for evaluating patients with COVID-19 [36,37]. Indeed, we reported the usefulness of LUS as the sole imaging modality with bedside accessibility to patients for the timely identi cation of pulmonary condition, thus reducing the risk of moving unstable ECMO patients [14]. Furthermore, de Almeida Monteiro et al showed a histological background that supports the fact that LUS can be used to characterise the progression and severity of lung damage in severe COVID-19 [38].…”
Section: Discussionmentioning
confidence: 84%
“…Several studies on the use of LUS in COVID-19 patients, which use CT as the reference standard, have indicated that LUS on admission may predict mortality or the need for invasive mechanical ventilation [13,14,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventilation management was performed with pressure-controlled ventilation driving pressure <14 and positive end-expiratory pressure (PEEP), based on a high PEEP table, from the acute respiratory distress syndrome (ARDS) net of respiratory frequency <15 [ 10 ]. FiO2 was adjusted to SpO2 >93%.…”
Section: Methodsmentioning
confidence: 99%
“…Lung ultrasound (LUS) is a rapid, bedside, goal-oriented, diagnostic test used to answer specific clinical questions, and its findings have been reported to be consistent with CT findings [ 7 , 8 ]. Moreover, LUS can be quantitatively assessed, and the serial LUS scores can be used to evaluate disease progression [ 9 , 10 ]. However, there is little knowledge of association of PMV and successful extubation using serial LUS scores.…”
Section: Introductionmentioning
confidence: 99%